The Political Technologies of Caste: Manufacturing a Caste Certificate in a Mumbai Slum. Issue 1 (2nd January 2016) - Shinde, Pradeep
ABSTRACT: This paper describes the political technologies of a caste certificate regularly employed by a Denotified Tribe, the Kunchikorves, in the Mumbai slum of Dharavi. The author demonstrates how the Kunchikorves mobilise kin and affine relations and engage with different organs of the state in an effort to authenticate their caste status. These 'caste certificates' are needed to make use of reservations policies to get government jobs and higher education. Municipal jobs and promotions are desirable as the basis for secure employment and upward mobility. Describing the circuitous methods by which the Kunchikorves obtain such authenticating documents, this paper notes that caste identity, while not hinging on notions of purity or pollution, is still an important vehicle for collective identification in contemporary India. The post-colonial state can be said to have extended and elaborated the colonial state's enumerating and objectifying imperatives when it comes to group identity. Groups such as the Kunchikorves are complicit in these objectifying measures, and actively seek out authenticating proofs of an identity that was originally pejorative, arbitrary and imposed. This paper argues that the Kunchikorves' manufacturing of caste certificates secures them a job, while at the same time bequeathing them a caste categorisation necessarily mediated by processes of bureaucratic authentication.